Bovine Pancreatic RNase A: An Insight into the Mechanism of Antitumor Activity In Vitro and In Vivo - Islam Saber Ead Mohamed; Aleksandra V. Sen'kova; Oleg V. Markov; Andrey V. Markov; Innokenty A. Savin; Marina A. Zenkova; Nadezhda L. Mironova (MDPI AG, 2022)
In this investigation, we extensively studied the mechanism of antitumor activity of bovine pancreatic RNase A. Using confocal microscopy, we show that after RNase A penetration into HeLa and B16 cells, a part of the enzyme remains unbound with the ribonuclease inhibitor (RI), resulting in the decrease in cytosolic RNAs in both types of cells and rRNAs in the nucleoli of HeLa cells. Molecular docking indicates the ability of RNase A to form a complex with Ku70/Ku80 heterodimer, and microscopy data confirm its localization mostly inside the nucleus, which may underlie the mechanism of RNase A penetration into cells and its intracellular traffic. RNase A reduced migration and invasion of tumor cells in vitro. In vivo, in the metastatic model of melanoma, RNase A suppressed metastases in the lungs and changed the expression of EMT markers in the tissue adjacent to metastatic foci; this increased Cdh1 and decreased Tjp1, Fn and Vim, disrupting the favorable tumor microenvironment. A similar pattern was observed for all genes except for Fn in metastatic foci, indicating a decrease in the invasive potential of tumor cells. Bioinformatic analysis of RNase-A-susceptible miRNAs and their regulatory networks showed that the main processes modulated by RNase A in the tumor microenvironment are the regulation of cell adhesion and junction, cell cycle regulation and pathways associated with EMT and tumor progression.